The role of heat shock proteins in neoplastic processes and the research on their importance in the diagnosis and treatment of cancer - Boliukh, Iryna; Rombel-Bryzek, Agnieszka; Żuk, Olga; Radecka, Barbara (Contemporary Oncology/Współczesna Onkologia, 2021)
Heat shock proteins (HSPs) are chaperones with highly conservative primary structure, necessary in the processes of protein folding to the most energetically advantageous conformation and maintaining their stability. HSPs perform a number of important functions in various cellular processes and are capable of modulating pathophysiological conditions at the cellular and systemic levels. An example is the high level of HSP expression in neoplastic tissues, which disrupts the apoptosis of transformed cells and promotes the processes of proliferation, invasion, and metastasis. In addition, an increasing amount of information is appearing about the participation of HSPs in the formation of multidrug resistance.This paper provides a review of the current state of research on the fundamental importance as well as the diagnostic and prognostic role of various classes of HSP in cancer treatment. It presents the prospects for using HSPs as biological markers of disease progression and targets in various cancer treatment strategies. However, the need for additional research is quite high. Only numerous joint efforts of research groups will allow the effective use of HSPs as a tool to combat cancer.